The effects of cleat location on muscle recruitment strategies of cycling - McDaniel, T. M.; Fu, Y. C.; Simpson, K. J. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
Foot placement may play an important role in muscle recruitment patterns and affect cycling performance. The purpose of this study was to determine if magnitude of activation increased in more proximal muscles when a more posterior compared to standard cleat location is used. Surface electromyography (8 muscles) and kinematics were collected from 11 experienced cyclists pedalling at 80 rpm rate during standard and posterior cleat location conditions. Root mean square (RMS) EMG were analyzed using paired t-tests. Peak RMS magnitude and crank angle of peak RMS were affected by cleat conditions. Posterior cleat locations alter the magnitude and muscular recruitment strategies of seated cycling when compared to neutral cleat placement.